Gastric Heterotopia Nasopharynx - Gurung, U; Shrivastav, A; Guragain, RPS; Bhusal, CL (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Heterotopia; nasopharynx, excision DOI: 10.3126/njenthns.v1i2.4761 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.21-22